2017
DOI: 10.3389/fpsyg.2017.02127
|View full text |Cite
|
Sign up to set email alerts
|

No Sensory Compensation for Olfactory Memory: Differences between Blind and Sighted People

Abstract: Blindness can be a driving force behind a variety of changes in sensory systems. When vision is missing, other modalities and higher cognitive functions can become hyper-developed through a mechanism called sensory compensation. Overall, previous studies suggest that olfactory memory in blind people can be better than that of the sighted individuals. Better performance of blind individuals in other-sensory modalities was hypothesized to be a result of, among others, intense perceptual training. At the same tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
(82 reference statements)
0
4
0
2
Order By: Relevance
“…This outcome suggests that episodic recognition for olfactory information is unrelated to blindness. Sorokowska and Karwowski (2017) recently showed similar findings for a large sample of blind and sighted participants who were tested shortly after encoding. It should be noted that although the effect of blindness on memory across time differed between the modalities, the interaction effect between retention interval, group, and modality was not statistically significant.…”
Section: Discussionmentioning
confidence: 53%
“…This outcome suggests that episodic recognition for olfactory information is unrelated to blindness. Sorokowska and Karwowski (2017) recently showed similar findings for a large sample of blind and sighted participants who were tested shortly after encoding. It should be noted that although the effect of blindness on memory across time differed between the modalities, the interaction effect between retention interval, group, and modality was not statistically significant.…”
Section: Discussionmentioning
confidence: 53%
“…The ability of people with certain disabilities to compensate for their limitations with hyper-developed abilities in other physical and sensory functions is well documented; for example, someone who is visually impaired will often demonstrate acute hearing or better memory (Sorokowska and Karwowski 2017). Relevant to this discussion, differences in the human experience noted in people with nonverbal autism include the response to and processing of sensory stimuli, which manifests as extreme sensitivity to visual, auditory or environmental input (Robertson and Baron-Cohen 2017).…”
Section: Spirituality and Languagementioning
confidence: 99%
“…Indeed, in the case of a forced-choice paradigm, the consensus is that blindness does not affect the performance (Smith et al, 1993;Rosenbluth et al, 2000;Schwenn et al, 2002;Cuevas et al, 2010;Beaulieu-Lefebvre et al, 2011;Luers et al, 2014;Comoglu et al, 2015;Gagnon et al, 2015;Sorokowska, 2016). However, in the case of a free naming identification task, several studies suggest that blind individuals outperform the sighted (Murphy and Cain, 1986;Rosenbluth et al, 2000;Wakefield et al, 2004;Cuevas et al, 2010;Rombaux et al, 2010;Renier et al, 2013;Gagnon et al, 2015), while only one team did not find significant results (Sorokowska, 2016;Sorokowska and Karwowski, 2017). Some authors have suggested that the heightened performance of blind individuals in free odor identification may be explainable by a greater ability for blind individuals to generate words (Burton et al, 2002), rather than from genuine increased olfactory ability.…”
Section: Introductionmentioning
confidence: 99%